Ganoderma diseases of perennial crops - Flood, J. (Julie); Bridge, P. D.; Holderness, M. (Mark) (Cabi Ser., 2000)
This book is a joint effort by 36 authors from 13 countries. The 19 chapters address many current issues in the development of sustainable disease management programmes and are grouped into five major themes. These are, an introduction to the pathogen and its systematics in chapters 1 and 2; outlines of the diseases (mainly on oil palms) caused by the pathogen (chapters 3-5); disease management (chapters 6-12); molecular biological variability in the pathogen (chapters 13-16); and the development of diagnostic tools (chapters 17-19). The majority of these chapters have been developed from presentations made at two international workshops on Ganoderma diseases held in Malaysia in 1994 and 1998, and a technical workshop held in the UK in 1998.